Policing Futures
X, 248 p.
Keywords: This innovative book offers a comprehensive assessment of policing in late modern Britain. The overall theme is that as we approach the end of the twentieth century, it is an appropriate time to review recent developments in policing and law enforcement and to consider future prospects.The areas covered include equal opportunities and public policework; perspectives on and politics of police policy making; the emergence and consequences of managerialism and privatisation; legitimacy, policing and human rights; crime control and surveillance in Northern Ireland; crime rates, victimisation and the provision of service; risk, late modernity and 'community policing'; regulating virtual communities and policing cybercrime; and the insights to be gained from comparative analysis. Thought-provoking and incisive, Policing Futures is an invaluable source of information, and will be essential reading for students, lecturers, researchers and practitioners in the fields of police studies, criminology, socio-legal studies, law, sociology, social policy, social work and related disciplines.